Histological Ex Vivo Evaluation of Peri-Incisional Thermal Effect Created by a New-Generation CO2 Superpulsed Laser. (25th February 2014) - Palaia, G.; Del Vecchio, A.; Impellizzeri, A.; Tenore, G.; Visca, P.; Libotte, F.; Russo, C.; Romeo, U.
Abstract : The purpose of this study is the evaluation of the histological effects of a new-generation superpulsed CO2 laser through an "ex vivo" study. A CO2 ( λ  = 10, 600 nm) ultra-speed laser (SmartUS20D, DEKA, Florence, Italy) has been used at different parameters from 2 to 4 watt in Continuous Wave (CW) and Pulsed Wave (PW, 50 Hz) to obtain 30 samples from pig cadaver tongues. All the specimens have been subdivided into 6 groups (from A to F) and each group consisted of 5 samples. A final specimen has been taken by scalpel and used as control group. Histological analysis has been performed using an optical microscope (Leica DM 2000) at a magnification of ×40. Results showed that histological readability was optimal in all the samples. The thermal damage has been negligible in all the groups. Furthermore, the average of thermal damage was 0, 095 mm in the epithelial, while it was 0.245 mm in the connective tissue. Statistical analysis using Graphpad Prism 5 software showed no significant differences among the groups. CO2 laser demonstrated a good surgical effectiveness provoking little peripheral damage onto the cut edges and allowing a safe histological diagnosis.